2023
DOI: 10.3390/robotics12060147
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Grape Harvesting Using Heterogeneous Autonomous Robots

Chris Lytridis,
Christos Bazinas,
Ioannis Kalathas
et al.

Abstract: The development of agricultural robots is an increasingly popular research field aiming at addressing the widespread labor shortages in the farming industry and the ever-increasing food production demands. In many cases, multiple cooperating robots can be deployed in order to reduce task duration, perform an operation not possible with a single robot, or perform an operation more effectively. Building on previous results, this application paper deals with a cooperation strategy that allows two heterogeneous ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…The manual labor-intensive process of hand-harvesting fruit is associated with substantial costs [46]. Advancing technologies related to grape-picking robots can enhance grape harvesting efficiency, mitigate labor costs and shortages, and bolster the economic viability of the grape industry [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…The manual labor-intensive process of hand-harvesting fruit is associated with substantial costs [46]. Advancing technologies related to grape-picking robots can enhance grape harvesting efficiency, mitigate labor costs and shortages, and bolster the economic viability of the grape industry [47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Over the past few years, there has been a significant expansion in the domains where robotics is employed. Beyond the conventional industrial applications such as material handling, welding, and machine tending, contemporary robotics finds its way into diverse sectors such as the construction sector [1], rescue robotics [2], agricultural [3,4] and food industry [5], waste management [6], entertainment [7], security systems [8], etc.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases, multiple cooperating robots can be deployed to reduce task duration, perform an operation not possible with a single robot, or perform an operation more effectively. In [11], a cooperation strategy is demonstrated that allows two heterogeneous robots to collaborate to harvest grapes, and its implementation is demonstrated. More specifically, the cooperative grape harvesting task involves two heterogeneous robots, where one robot (i.e., the expert) is assigned the grape harvesting task, whereas the second robot (i.e., the helper) is tasked with supporting the harvesting task by carrying the harvested grapes.…”
mentioning
confidence: 99%